Vitamin C intake and osteoarthritis: findings of NHANES 2003–2018 and Mendelian randomization study - Zhang, Hongjie; Jiang, Xuan; Bai, Lei; Chen, Jiahui; Luo, Wei; Ma, Jianxiong; Ma, Xinlong (Frontiers in Nutrition, 2024)
Background The role of vitamin C in osteoarthritis (OA) is still a subject of debate. Our aim was to combine the National Health and Nutrition Examination Survey (NHANES) and MR studies to explore the relationship between Vitamin C intake and OA. Methods Clinical information on participants during NHANES 2003-2018 was collected and the relationship between vitamin C intake and OA risk was assessed using logistic regression modelling. In MR analyses, three methods were used to explore the causality of vitamin C intake with OA. Sensitivity analysis to verify the stability of the MR study. Results The cross-sectional study included a total of 31,527 participants, categorizing them into low (< 30.2 mg), medium (30.2-93.0 mg) and high (>93.0 mg) level groups based on their vitamin C intake levels. Logistic regression models showed that vitamin C intake was not associated with OA risk (p>0.05). Inverse-variance weighted (IVW) method of MR study showed no causality between vitamin C intake and OA (OR= 0.993, 95% CI: 0.901 1.095, p = 0.882). Sensitivity analysis indicated that the MR study was reliable Conclusions Our cross-sectional and MR studies showed that vitamin C intake was not associated with OA risk. More researches are needed in the future to investigate the link between vitamin C and OA.